Costa Rica : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
The economy recovered quickly from the global crisis of 2008-09, with healthy growth and low inflation. Growth has, however, slowed recently and is expected to remain subdued in the short run, since gains from recovery in the U.S. will be offset by the closure of the Intel manufacturing plant. Inflation is elevated, owing primarily to exchange rate (XR) depreciation triggered by global repricing of emerging market assets in early 2014. Risks to the outlook are tilted to the downside. Absent consolidation, large fiscal deficits would make public debt dynamics unsustainable in the long-run.